Welfare Economics and Cultural Analysis: Islamic Perspectives on Barber Shops - Maguni, Wahyudin; Abdul Kadir, H.; Herman, H.; Ummi Kalsum, Hj.; M. Hadi, H.; ., Sumiyadi; Laban, Imran; Adzil, Adzil; Ahmad, Yusrifal (KnE Social Sciences, 2022)
Barber shop businesses are increasingly mushrooming in average cities and big cities. We can see that many exist in almost every segment and road. Barber shops are commonly made with a box house model with a medium size, dominated by glass and spandex. It is important to examine in depth whether this trend is part of long-standing cultural factors, or is the influence of a global culture promoting the idea that everyone needs a barber shop to keep their appearance updated and current, or is a side culture that was born out of current economic conditions. Another element to consider is the view of Islam, and the value of measurement in pursuing economic value and welfare. The barber shop culture seems to be a reflection of the habits of people living in developing cities and other big cities. Keywords: welfare economics, culture and Islamic perspective, barbershop